2023
DOI: 10.1071/bt22126
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight and red to far-red ratio impact germination of tropical montane cloud forest species

Abstract: Context Australia’s tropical montane cloud forests (TMCF) exhibit exceptional species richness and endemism. Determinants of regeneration via seed of these species are next to unknown, limiting our ability to quantify and project their vulnerability to climate change. The ratio of red to far-red light (R:FR) has been shown to influence seed germination of many tropical species. Aims We investigated germination of six previously unstudied TMCF species in relation to the presence or absence of light (lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
0
0
Order By: Relevance
“…These new insights show how the regeneration niche may contribute to species distribution under climate change. For example, Hoyle et al (2023) demonstrated that light quality, which is likely to be altered by reduced cloud immersion, impacts the germination responses of tropical montane cloud forest species from far-north Qld. Coupled with innovative technology like temperature gradient plates (Collette et al 2021), research can test multiple levels of factors and enable high resolution investigations of environmental drivers of germination.…”
Section: Australasian Seed Science Conference (Assc)mentioning
confidence: 99%
“…These new insights show how the regeneration niche may contribute to species distribution under climate change. For example, Hoyle et al (2023) demonstrated that light quality, which is likely to be altered by reduced cloud immersion, impacts the germination responses of tropical montane cloud forest species from far-north Qld. Coupled with innovative technology like temperature gradient plates (Collette et al 2021), research can test multiple levels of factors and enable high resolution investigations of environmental drivers of germination.…”
Section: Australasian Seed Science Conference (Assc)mentioning
confidence: 99%